COMPARATIVE ANALYSIS OF SOLID WASTE MANAGEMENT IN SELECT CAMPUSES OF A STATE UNIVERSITY IN THE VISAYAS REGION, PHILIPPINES - Abaquita, Ma. Carla Y; Mendoza, Siegfried D (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Solid waste management requires serious attention. Environmental education brings awareness, appreciation, understanding, and solutions for us to transition to a more sustainable society. With the aim of finding a workable solution, this study on the comparative analysis of solid waste management in select campuses of a certain state university in Cebu was conducted. This involved a contextual review and qualitative analysis of the waste generation rates and waste composition data as to biodegradable, recyclable/reusable, residual, and special/hazardous wastes; physical areas such as environment and disposal, and resource recovery; and governance strategies such as inclusivity, financial sustainability, and proactive policies. The results showed residual wastes had the highest total weight of 1.47 kg while the hazardous wastes had the lowest total weight of 0.28 kg based on the capita waste production daily of the nine campuses. The average daily waste generation rate per capita ranged from 0.22 to 0.53 kg. The campuses observed a similar process of waste collection of at least twice a week. Separate receptacles were provided for waste segregation from source but not sustained in the dumpsites. Wastes were disposed of in one open dumpsite. The Material Recovery Facilities (MRF) were not fully functional. Open burning was practiced by some campuses. There was a low score in waste collection coverage; consultation and involvement of users in decision-making on policy and solid waste management programs, planning of facilities; procedures for measuring satisfaction, and effective feedback mechanism. A lack of proactive policies existed. Integration of solid waste management in the curriculum is vital for sustainability goals.